Body Image Disturbance and Health Behaviors among Sexual Minority Men Living with HIV - Blashill, Aaron J. (2014)
OBJECTIVE: Body image disturbance is a common experience for sexual minority men living with HIV, and is associated with poor self-care behaviors. However, to date, no known cohesive theoretical model has been advanced to understand the possible antecedents and outcomes of body image disturbance in this population. Thus, the goal of the current study was to test a biopsychosocial model of body image and self-care behaviors among sexual minority men living with HIV. METHODS: Participants were 106 gay and bisexual men living with HIV who completed a battery of self-report measures including assessment of body image disturbance, depression, lipodystrophy, appearance orientation, condom use self-efficacy, antiretroviral therapy (ART) adherence, and HIV sexual transmission risk behaviors. Bayesian estimation was employed to assess model fit and direct and indirect pathways within the model. RESULTS: The data fit the model well, with all theorized pathways being significant. Lipodystrophy severity and appearance orientation were associated with elevated body image disturbance. In turn, body image disturbance was related to poorer ART adherence and increased HIV sexual transmission risk behaviors, through the mechanisms of elevated depressive symptoms and poor condom use self-efficacy. CONCLUSIONS: Elevated body image disturbance among sexual minority men living with HIV is associated with important biopsychosocial variables, which in turn are related to poorer ART adherence and increased HIV sexual transmission risk behaviors. Integrative psychosocial interventions addressing co-occurring body image disturbance, depression, and HIV self-care behaviors may be a fruitful area of future clinical practice and research.